(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of ensuring the stability of the socio-spiritual environment in society, victimological prevention and its dialectical features in ensuring the stability of the socio-spiritual environment in society, and the prospects for improving the victimological prevention system in ensuring the stability of the socio-spiritual environment. Modern conceptual approaches and views on ensuring the stability of the socio-spiritual environment in society are also analyzed.